MENTORING AS AN HR INTERVENTION TO ENGAGE GEN Y EMPLOYEES - Naim, Mohammad Faraz; Lenka, Usha (PEOPLE: International Journal of Social Sciences, 2016)
The significance of employee engagement in present turbulent business environment cannot be over-emphasized. In particular, the contemporary mutigenerational workforce poses a serious challenge of employee engagement. The importance of mentoring in facilitating employee development, socialization, and is given due consideration in academic literature. However, the literatures on mentoring and employee engagement are largely independent. In this vein, this study explores the linkage between mentoring and employee engagement. After reviewing the limited literature in this domain a conceptual framework is proposed depicting possible relationships through testable propositions. To conclude implications are presented for human resource development (HRD) scholars and practitioners, emphasizing on the role of mentoring in fostering cognitive, affective, and social aspects of Gen Y employees’ engagement.